Indonesian representation in South Korean media during the Asian Games Jakarta – Palembang 2018 - Safira Ronasyifa; Didin Samsudin (Universitas Pendidikan Indonesia (UPI), 2022)
In August 2018, Indonesia hosted the Asian Games Jakarta – Palembang 2018. After hosting in 1962, Indonesia has had the theme